An introduction to Tamil racism in Sri Lanka - Da Silvā, Nalin (Maharagama : Chintana Prashadaya, 1997)
Study of the evolution of the Tamil ethnic problem in Sri Lanka, dating to the early 20th century, in the form of questions and answers.
Keywords: Tamil (Indic people) -- Sri Lanka -- Politics and government; Sri Lanka -- Ethnic relations; Sri Lanka -- Politics and government